1999
DOI: 10.1080/109158199225404
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase-Mediated N-Demethylation of Imipramine and Related Tricyclic Antidepressants in the Presence of Hydrogen Peroxide

Abstract: In this study, we examined the ability of soybean lipoxygenase to mediate the N-demethylation of imipramine and related drugs in the presence of hydrogen peroxide. Formaldehyde generation resulting from the N-demethylation of imipramine, a prototype drug, was found to depend on incubation time, and the concentration of the enzyme, imipramine, and hydrogen peroxide. Under optimal assay conditions, Vmax values of 14 to 18 nmol formaldehyde/min/nmol enzyme or 133 to 164 nmol formaldehyde/min/mg protein were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Thus, in theory, the intracellular accessibility of imipramine is expected to be much higher to LO than to P450, MFMO, or PGS. The reported LO-mediated extensive N-demethylation of imipramine [61] strongly supports this view. Although a demonstration of the presence of P450 in trace amounts, for example, may be of some academic interest, the efficiency of the enzyme, in a practical sense is far more important and should not be ignored.…”
Section: Importance Of Lo-mediated Xenobiotic Metabolismsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, in theory, the intracellular accessibility of imipramine is expected to be much higher to LO than to P450, MFMO, or PGS. The reported LO-mediated extensive N-demethylation of imipramine [61] strongly supports this view. Although a demonstration of the presence of P450 in trace amounts, for example, may be of some academic interest, the efficiency of the enzyme, in a practical sense is far more important and should not be ignored.…”
Section: Importance Of Lo-mediated Xenobiotic Metabolismsupporting
confidence: 71%
“…Since LO activity occurs in the liver and brain [55,122], its involvement in imipramine oxidation can be suspected. Exploration of this hypothesis revealed that imipramine is an excellent substrate for N-dealkylation by SLO in the presence of H 2 O 2 [61]. Desipramine, the expected product of imipramine mono N-demethylation, was identified by HPLC.…”
Section: Dealkylationmentioning
confidence: 99%
“…In light of these observations, a hypothesis that LO may be involved was tested using SLO. The results indicated that imipramine is an excellent substrate and undergoes dealkylation at the rate of ~114 nmoles/min/mg SLO in the presence of H 2 O 2 [174]. Desipramine, the expected product of imipramine mono Ndemethylation, was identified by HPLC.…”
Section: Drugsmentioning
confidence: 98%
“…However, they too have been found to be able to undertake the metabolism of a variety of xenobiotic substrates. In various studies, lipoxygenase was shown to act upon several tricyclic drugs including amitryptiline, chlorpromazine, doxepin, imipramine, promazine and promethazine [87][88][89][90] in addition to oxyphenbutazone [91] and phenytoin [92]. Similarly, prostaglandin H-synthase catalysed the biotransformation of many xenobiotic compounds as well as the drugs, aminopyrine [93], diethylstilboestrol [94,95], oestradiol [96], phenylbutazone [97] and sulindac sulfide [98,99].…”
Section: Reflections On the Futurementioning
confidence: 99%